Penerapan Akad Murabahah pada Produk Pembiayaan KPR (Studi Kasus Bank BTN Syariah Kcps Pekalongan) - Fajar Sodik; Rikhadatun Abir Al Farda; Elisa Ayuni (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2023)
Home is a basic human need. Islamic banking has the option to provide Home Ownership Loans (KPR), namely sharia mortgages from Islamic banks known as Home Ownership Financing (PPR). This study discusses the application of murabahah contracts in mortgage financing at Bank BTN Syariah KCPS Pekalongan. Bank BTN Syariah is a conventional Bank BTN-based business unit that has implemented a murabahah contract in mortgage financing. This study aims to determine the application of the murabahah contract in mortgage financing at Bank BTN Syariah KCPS Pekalongan. This study uses a type of qualitative research in the form of descriptive. The data used are primary data and secondary data. The data in this study were obtained from observations, interviews and documentation. The analysis technique used is an interactive model with the following stages: data reduction, data display and drawing conclusions. The results of this study indicate that the murabahah contract has been implemented properly because the elements of the murabahah contract are in accordance with the fatwa of the national sharia board. Empirically, the implications of the results of this study are expected to be input for Bank BTN Syariah Kcps Pekalongan as consideration for encouraging more sharia mortgage products while making it easier for customers to take sharia mortgages. Another implication of the results of this research is theoretically expected to be able to contribute ideas in the development and improvement of science.